1-Deazaadenosine: synthesis and activity of base-modified hammerhead ribozymes. - Seela, F (1998)
The incorporation of 1-deazaadenosine (c1A, 1b) into a hammerhead ribozyme and the resulting catalytic activity is described. For this purpose the phosphoramidite 2a and the 3'-phosphonate 2b as well as Fractosil-linked 1-deazaadenosine (3b) were prepared. The methoxyacetyl group was used for the 6-amino group protection and the triisopropylsilyl residue was introduced as the 2'-OH protecting group. Replacement of residues A14and A15.1 of the hammerhead ribozyme by 1-deazaadenosine resulted in a significantly reduced catalytic activity. Substitution of the A6, A9 and A13 residues has only a minor influence. The findings observed on ribozymes modified with 1-deazaadenosine were compared with those containing other adenosine analogues.